THE INFLUENCE OF ONLINE AND MANUAL DICTIONARY USE, AND INITIAL SKILLS ON ENGLISH LEARNING OUTCOMES OF XITH CLASS STUDENTS SMA NEGERI 1 KAWEDANAN MAGETAN DISTRICT - Suaidah, Masning; Noor Fatirul, Ahmad; Adi Waluyo, Djoko (LPPM STAI Muhammadiyah Probolinggo, 2023)
In practice, almost all students experience problems in learning of all English skills. In order for the problems that arise to be an option, one factor that needs to be considered is the use of media in the form of dictionaries, both online dictionaries and manual dictionaries as well as measuring students' initial abilities, in order to improve learning results. The aims of this study are: 1) To determine the effect of using online dictionaries and manual dictionaries and initial abilities on English learning outcomes, 2) To determine the differences in English learning outcomes for class XI students between students who have high initial abilities and students who have low initial abilities, 3) To determine the interaction between dictionary use and initial abilities on English learning outcomes. This study used an experimental design method. The samples in this study were 120 students of XI class at SMA Negeri 1. Data collection method that used was test. Data analysis in this study used a two-way Anava test. The results showed that the use of dictionaries and initial skills proved to have an influence on the results of learning English in XI class students of SMA Negeri 1 Kawedanan Magetan. The suggestion from this research is that students are expected to be able to improve their ability in English lessons, especially in understanding a text through the use of dictionary so that it can improve students' skills in English and provide good learning outcomes.